Efficacy and tolerability of EPs 7630 in children and adolescents with acute bronchitis: a randomized, double-blind, placebo-controlled multicenter trial with a herbal drug preparation from Pelargonium sidoides roots - Kamin, Wolfgang; Maydannik, V.; Malek, F.A.; Kieser, Meinhard (International journal of clinical pharmacology and therapeutics, 2010)
The study aim was to demonstrate the efficacy and to investigate the tolerability of EPs 7630, a herbal drug preparation from Pelargonium sidoides roots, in the treatment of patients (1 – 18 years) with acute bronchitis outside the strict indication for antibiotics.